Sea surface height fluctuations relevant to Indian summer monsoon over the northwestern Indian Ocean - Zhang, Xiaolin; Mochizuki, Takashi (Frontiers in Climate, 2022)
We examined the interannual variations in sea surface height (SSH) over the northwestern Indian Ocean during 1993–2016, by using in situ observations along the east coast of the Arabian Peninsula together with satellite observations, objective analysis, and reanalysis. Focusing on the impacts of the Indian summer monsoon relative to the El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) modes, we found that the monsoon predominantly controls the summertime SSH variations at the in situ observatories, consistent with satellite observations. The monsoon is closely related to the SSH at a specific observatory in almost all seasons, whereas the wintertime SSH is strongly influenced by ENSO and IOD at other observatories. These SSH variations with local modulations in the coastal area were accompanied by basin-scale variations. The reduced southwesterly monsoon wind, for example, is found with the reduced ocean upwelling narrowly confined near the coast and the upper ocean temperature rise implying reduced meridional heat transport over the south of the Arabian Peninsula.